THE BOY'S SELF-CONCEPT IN ALICE CHILDRESS' THE WORLD ON A HILL - Asih Pujiyanti Linusia Marsih (Universitas 17 Agustus 1945 Surabaya, 2014)
This study reports an analysis of self-concept in Alice Childress’ drama entitled The World on a Hill. The focus of the study is the main character identified as The Boy or Winston. The problems to be investigated in the study are (1) What is The Boy’s self-concept?, (2) What factors affect The Boy’s self-concept?, and (3) How does The Boy’s self-concept develop? The study adopts both intrinsic (character) and extrinsic (psychological) approaches and is designed as a descriptive qualitative research. The results of the study show that the self-concept of the main character (the Boy) has Impacts toward his Behaviors and Mannerism. Also, there are at least three factors that affect his self-concept: physical appearance, goals and expectation and family condition. The boy’s self-concept develops from his understanding and acceptance of his weaknesses and strengths and then begins to set priorities in life to make his dream come true.